Case reportOmalizumab treatment in brittle asthma - Skiepko, Roman; Zietkowski, Ziemowit; Skiepko, Urszula; Budny, Wojciech; Lukaszyk, Mateusz; Bodzenta-Lukaszyk, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Asthma is a heterogeneous disease with variable characteristics such as lung function, symptoms and control, body weight, pattern of inflammation, and response to treatment. Brittle asthma is one of clinical phenotypes of asthma with unclear pathogenic mechanisms and appropriate treatment. Analysis of 2 described cases suggests that omalizumab could be useful in the treatment of brittle allergic asthma.